Evaluation of a Li-Titanate battery module in primary frequency control ancillary service conditions. (August 2019) - Sergi, F.; Brunaccini, G.; Aloisio, D.; Randazzo, N.; Polito, R.M.; Pietrucci, M.; Fadda, M.G.; Ferraro, M.; Antonucci, V.
Highlights: A lithium-Titanate battery module was tested for 250 days under frequency control endurance test profile. No variation in both the discharged capacity and in discharged energy was found. The Li-Titanate battery module is good for primary frequency control dynamics. The module energy content is not sufficient for one-day continuous operation in primary frequency control conditions. The tool developed suggests to oversize the energy content up to 1.5C/Cn - 2C/Cn for continuous service availability. Abstract: Power networks are deeply changing in recent years due to the rapid deployment of renewable energies and a growing worldwide energy demand. Energy storage systems are promising technologies to provide electric networks with ancillary services. Currently, only few data referred to batteries operation in power network ancillary services utilization are available. This could limit the evaluation of battery technologies in relation to those applications. Li-Titanate technology is characterized by a high specific power, long lifetime, and it guarantees high safety in stressful conditions. In this framework, the performance of a Li-Titanate battery module, subjected to a Primary Frequency Control (PFC) cycle, was studied. This paper reports the results coming from the testing campaign, where Li-Titanate battery demonstrated no degradation after 250 test days. Due to the module low energy content with respect the PFC profile, the battery resulted discharged two times per day. Therefore, a numerical tool was developed in order to obtain a valid instrument for optimal design in relation to PFC application and for simulating Li-Titanate battery module behavior.